2022
DOI: 10.1021/acsomega.1c07158
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Iron Oxide Nanoparticle-Modified APTES-ITO Electrode for Simultaneous Stripping Analysis of Cd(II) and Pb(II) Ions

Abstract: Carboxyl (−COOH)-stabilized iron oxide nanoparticles (IONPs) synthesized through co-precipitation were used to modify an indium tin oxide (ITO) electrode, which was chemically functionalized with 3-aminopropyltriethoxysilane (APTES) for heavy metal detection. The effect of soaking time (30, 60, 90, and 120 min) of IONP-COOH self-assembled on an APTES-ITO electrode was studied. Cyclic voltammetry and scanning electron microscopy were applied to analyze the electrochemical properties and morphologies of IONP-COO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…During the modification process, the ethoxy functional group in the APTES molecule undergoes hydrolysis to form silanols (SiOH). These silanols can be immobilized by covalent bonding with magnetite Fe 3 O 4 NPs 35 . Therefore, the silanols formed through hydrolysis of the ethoxy functional group in the APTES molecule can be covalently bonded with the magnetite Fe 3 O 4 NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the modification process, the ethoxy functional group in the APTES molecule undergoes hydrolysis to form silanols (SiOH). These silanols can be immobilized by covalent bonding with magnetite Fe 3 O 4 NPs 35 . Therefore, the silanols formed through hydrolysis of the ethoxy functional group in the APTES molecule can be covalently bonded with the magnetite Fe 3 O 4 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…These silanols can be immobilized by covalent bonding with magnetite Fe 3 O 4 NPs. 35 Therefore, the silanols formed through hydrolysis of the ethoxy functional group in the APTES molecule can be covalently bonded with the magnetite Fe 3 O 4 NPs. Moreover, the observed Fe O peak at 585 cm À1 indicating the formation of Fe 3 O 4 NPs which correlate with Raman analysis.…”
Section: Physiochemical Properties Of Mmmsmentioning
confidence: 99%
“…Nor et al 172 designed an electrochemical sensor method based on carboxyl iron oxide nanoparticles (IONPs) for detecting Cd( ii ) and Pb( ii ) in seawater samples. In this report, the indium tin oxide (ITO) electrode functionalized with 3-aminopropyltriethoxysilane (APTES) was modified by carboxyl iron oxide nanoparticles.…”
Section: Iron and Iron-oxide Magnetic Nanoparticle-based Electrochemi...mentioning
confidence: 99%
“…Table 1 ref. 50–175 summarizes the types of food contamination studied using the electrochemical sensors based on iron magnetic beads.…”
Section: Introductionmentioning
confidence: 99%
“…Their studies reported on single heavy metal detection. Recently, they reported on an iron oxide nanoparticle-modified APTES-ITO electrode for the simultaneous detection of Cd(II) and Pb(II) 27 and bismuth nanosheet-modified APTES-SPCE for Pb(II) detection with excellent electrochemical performance. 28 Inspired by the excellent properties of APTES, in this work, AuNPs assembled with varying concentration percentages on the chemically functionalized APTES-ITO electrode for the simultaneous detection of Cd(II), Pb(II), and Cu(II) were studied.…”
Section: Introductionmentioning
confidence: 99%